Nitrogen (N2) removal in gas separation using polysulfone membrane - Nur Ariffah, Md Sani (2010)
The development of membrane separation process in gas separation process has recently gained numerous interests from industries. With low capital and operating cost, operational simplicity, high reliability, space efficiency and environmental friendly, the membrane technology is the best candidate to replace traditional gas separation methods. Polysulfone polymer potentially, can be use as membranes for nitrogen removal in gas separation with very high mechanical and thermal strength which can be applied at wide range of temperature and pressure. The polysulfone membrane was prepared by mixing polysulfone pellet with N,N-dimethylacetamide (DMAc) solvent to dilute the polymer before it is cast using casting knife into smaller samples. Samples of membrane with different polymer composition were produce. Then the already cast membrane was immersed in different coagulation bath and finally the samples undergo permeability test using membrane permeation unit to etermine the permeability and selectivity of each membrane. High polymer composition and coagulation bath temperature will produce high selectivity membrane but low permeability membrane and so vice versa. The most ideal membrane must have high permeability and selectivity. Thus, the olysulfone membrane with 25wt% polymer composition immersed in room temperature tap water, is chosen as the best membrane to separate N 2 from CO 2,02,and C114.